Identification of the early and late responder genes during the generation of induced pluripotent stem cells from mouse fibroblasts. - Jihwan Park; Yoo-Wook Kwon; Seokjin Ham; Chang-Pyo Hong; Seonghye Seo; Moon Kyung Choe; So-I Shin; Choon-Soo Lee; Hyo-Soo Kim; Tae-Young Roh (PLoS ONE, 2017)
Background The generation of induced pluripotent stem cell (iPSC), a substitute for embryonic stem cell (ESC), requires the proper orchestration of a transcription program at the chromatin level. Our recent approach for the induction of pluripotent stem cells from fibroblasts using protein extracts from mouse ESCs could overcome the potential tumorigenicity risks associated with random retroviral integration. Here, we examine the epigenetic modifications and the transcriptome of two types of iPSC and of partially reprogrammed iPSCs (iPSCp) generated independently from adult cardiac and skin fibroblasts to assess any perturbations of the transcription program during reprogramming. Results The comparative dissection of the transcription profiles and histone modification patterns at lysines 4 and 27 of histone H3 of the iPSC, iPSCp, ESC, and somatic cells revealed that the iPSC was almost completely comparable to the ESC, regardless of their origins, whereas the genes of the iPSCp were dysregulated to a larger extent. Regardless of the origins of the somatic cells, the fibroblasts induced using the ESC protein extracts appear to be completely reprogrammed into pluripotent cells, although they show unshared marginal differences in their gene expression programs, which may not affect the maintenance of stemness. A comparative investigation of the iPSCp generated by unwanted reprogramming showed that the two groups of genes on the pathway from somatic cells to iPSC might function as sequential reprogramming-competent early and late responders to the induction stimulus. Moreover, some of the divergent genes expressed only in the iPSCp were associated with many tumor-related pathways. Conclusions Faithful transcriptional reprogramming should follow epigenetic alterations to generate induced pluripotent stem cells from somatic cells. This genome-wide comparison enabled us to define the early and late responder genes during the cell reprogramming process to iPSC. Our results indicate that the cellular responsiveness to external stimuli should be pre-determined and sequentially orchestrated through the tight modulation of the chromatin environment during cell reprogramming to prevent unexpected reprogramming.